Avaliação do impacto dos diferentes usos do solo nas emissões de C-CO2 na região de planalto de Santarém, Pará - FERREIRA JUNIOR, Miércio Jorge Alves (Universidade Federal do Oeste do Pará, 2021)
The flow of carbon dioxide (CO2) depends on the ratio between production and consumption, and diffusion in the soil. The production and emission of CO2 in native areas, pastures and cultivated, is the result of microbial activity and mineralization of organic matter, and depends on favorable environmental factors such as temperature, water availability and land use. In this study, we evaluated the impact of changing coverage on the efflux of C-CO2 pastures and forests in the plateau area of Santarem, Para used the method of dynamic chambers associated with infrared gas analyzer. The results of this work show that the system tillage (NT) has the potential to mitigate in 37,7% participation in agriculture C-CO2 efflux of soil-based cultivation of soy without the intense tillage as in Planting conventional (PC). The temperature of the soil accounted for 65% of the variability of the flow of CO2 in the C-PC. The variation of soil moisture explained 73% and 51% to the flux of C-CO2 in PC and PD, respectively. These results indicate that soil moisture and soil temperature were controlling factors of CO2-C emissions from soil to atmosphere because these parameters directly affect soil microbial activity. The results also show that the active pasture had the highest outflows of C-soil CO2 to the atmosphere in relation to forests and degraded pasture in Western Pará. urthermore, it was shown that both the pastures and forests have a seasonality in the flow, which should be mainly related to precipitation patterns and water potential between soil and air. We observed a strong correlation between the efflux and soil moisture of both capoeira and in the pastures, as the soil temperature was a controlling factor of the active efflux only in the pasture. The average flow of C-CO2 obtained in pasture active was 218,9 mg m-2 h-1 value of 40,7% higher than the primary forests and 155,5 mg m-2 h-1 . Finally, the results presented here suggest that the conventional tillage and pasture management active, activities strongly associated to human enhance biogeochemical changes in the balance of carbon in these ecosystems, since the efflux of C-CO2 is related to soil productivity primary of these ecosystems.